Influence of cigarette smoking on pemphigus – a systematic review and pooled analysis of the literature. (13th March 2018) - Lai, O.; Recke, A.; Zillikens, D.; Kasperkiewicz, M.
Abstract: Epidemiological evidence suggests that smoking cigarettes may be beneficial in pemphigus, but no systematic evaluation exists to corroborate this assumption. Therefore, a systematic literature review with pooled data analysis of the smoking status in patients with pemphigus was conducted. Electronic searches using PubMed from inception to November 2017 identified 13 reports meeting predetermined inclusion and exclusion criteria. Most were case–control studies partly reporting that pemphigus vulgaris and foliaceus occurred less frequently in current and former smokers. Studies also indicated that duration of smoking and number of cigarettes smoked were lower in patients with pemphigus than controls and that remission may be achieved sooner in those who smoke. However, although a generally low prevalence of smoking was demonstrated in patients with pemphigus, which was lower than in controls by pooled analysis, some investigations found no difference regarding the smoking status compared with non‐pemphigus subjects. One study demonstrated more severe mucosal involvement in non‐smoking patients with pemphigus, whereas another observed no difference in the rate of cutaneous or mucosal lesions between smokers and non‐smokers with pemphigus. This review indicates that smoking may be a possible protective factor in pemphigus, although some compromised study methodologies yet hinder any firm conclusion. Further investigations with a refined quality design are required to resolve the so far partly conflicting results in this area.